The Medical, Agricultural and Economic Importance of Albisia Julibrissin - Yassin, Shrook Gany; Sgheer, Suhad Khalid (American Journal of Biology and Natural Sciences, 2025)
The use of the Albizia plant in traditional medicine by various countries around the world is of great importance due to the potential health benefits it can provide. Different portion of the plant are employed for their various medicinal uses, including the treating of conditions such as asthma, cough, and digestive disorders. It is noteworthy that the active compounds present in the plant have anti-inflammatory and antibacterial properties, in addition to antioxidant effects. Economically, the Albizia plant is of great importance as it is used in the production of wood, which is a valuable resource used in construction, furniture manufacturing, and the manufacture of various wood products. It also contributes to supporting biodiversity by providing habitats for many birds and insects. The plant shows importance in regulating shade and local climate, as Albizia trees provide wide shade, contributing to a cooler local climate. In this study, the medical, economic, and environmental importance of the Albizia plant is reviewed.